Ethylene Acts as a Local and Systemic Signal to Mediate UV-B-Induced Nitrate Reallocation to Arabidopsis Leaves and Roots via Regulating the ERFs-NRT1.8 Signaling Module - Wang, Xiao-Ting; Xiao, Jun-Hua; Li, Li; Guo, Jiang-Fan; Zhang, Mei-Xiang; An, Yu-Yan; He, Jun-Min (International journal of molecular sciences, 2022)
Nitrate is the preferred nitrogen source for plants and plays an important role in plant growth and development. Under various soil stresses, plants reallocate nitrate to roots to promote stress tolerance through the ethylene-ethylene response factors (ERFs)-nitrate transporter (NRT) signaling module. As a light signal, ultraviolet B (UV-B) also stimulates the production of ethylene. However, whether UV-B regulates nitrate reallocation in plants via ethylene remains unknown. Here, we found that UV-B-induced expression of ERF1B, ORA59, ERF104, and NRT1.8 in both Arabidopsis shoots and roots as well as nitrate reallocation from hypocotyls to leaves and roots were impaired in ethylene signaling mutants for Ethylene Insensitive2 (EIN2) and EIN3. UV-B-induced NRT1.8 expression and nitrate reallocation to leaves and roots were also inhibited in the triple mutants for ERF1B, ORA59, and ERF104. Deletion of NRT1.8 impaired UV-B-induced nitrate reallocation to both leaves and roots. Furthermore, UV-B promoted ethylene release in both shoots and roots by enhancing the gene expression and enzymatic activities of ethylene biosynthetic enzymes only in shoots. These results show that ethylene acts as a local and systemic signal to mediate UV-B-induced nitrate reallocation from Arabidopsis hypocotyls to both leaves and roots via regulating the gene expression of the ERFs-NRT1.8 signaling module.